A new Neotropical species of Tanytarsus van der Wulp, 1874 (Diptera: Chironomidae), with an unusual anal process - Trivinho-Strixino, Susana; Strixino, Giovanni (Zootaxa, 2007)
Male, female, pupa and larva of Tanytarsus caipira sp. n. are described and figured. Larvae were collected on the aquatic macrophyte Mayaca fluviatilis in a small pond in southeastern Brazil and reared to the adult stage. The male of T. caipira can be distinguished from all other described Tanytarsus species by the lack of a proper anal point and the long, forked, dorsal anal process. The pupa differs from other Tanytarsus species in having 2 pairs of taeniate setae on sternite VIII. The larva of T. caipira has a large Lauterborn organ placed on a short, weakly sclerotized pedicel.